2023
DOI: 10.1021/acs.jafc.3c01678
|View full text |Cite
|
Sign up to set email alerts
|

Fluidized-Bed-Roasted Cocoa Has Different Chemical Characteristics than Conventionally Roasted Cocoa

Abstract: The roasting process can modulate sensory and physicochemical characteristics of cocoa. This study compared the chemical characteristics of cocoa nibs roasted by a convective oven [slow roasting(SR)] vs cocoa nibs roasted in a fluidized bed roaster [fast roasting(FR)] at two temperatures (120 and 140 °C). The contents of sugars, free amino acids (FAAs), polyphenols, acrylamide, 5-hydroxymethylfurfural, and melanoidins were monitored. Roasting reduced fructose, glucose, and sucrose contents by 95, 70, and 55%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…The MR involves a series of interactions between the carbonyl group in a reducing sugar or oxidized lipid and the amino group in amino acids, peptides, or proteins. It was reported that the cysteine content in BG is 5 times higher than that in white garlic [7]. However, the changes in amino acids in BG MLDs during storage are little-studied.…”
Section: Introductionmentioning
confidence: 99%
“…The MR involves a series of interactions between the carbonyl group in a reducing sugar or oxidized lipid and the amino group in amino acids, peptides, or proteins. It was reported that the cysteine content in BG is 5 times higher than that in white garlic [7]. However, the changes in amino acids in BG MLDs during storage are little-studied.…”
Section: Introductionmentioning
confidence: 99%